Stereometric and Planimetric Interpretations of Language Sign - GYULZATYAN, DAVIT (Bulletin of Yerevan University B: Philology, 2021)
The existence of the semiosphere which includes the sign and nonsign components is balanced by the relativity of logical space; whatever is the space of some planes, in turn, can become the plane of another space. The spatial and planar parameters of a linguistic sign are inherent in all linguistic types, systems, their ontological and structural levels, and transitions between these levels. Stereometric and planimetric interpretations are identified by using the language code. The latter for the language is the same as for automatic systems, their procedures, from the moment of launch to completion. The language code is an organization which is inherent in the entire language composition, which includes all the patterns necessary to realize the intentions of the given composition.